RANCANG BANGUN ANTENA MIKROSTRIP PATCH CIRCULAR DENGAN TEKNIK LINIER ARRAY UNTUK FREKUENSI WIFI 2,4 GHZ - Saputra, Surya Hadi; Jayati, Ari Endang; Erlinasari, Erlinasari (Universitas Semarang, 2019)
Microstrip antenna when the antenna is one of the very rapid development in telecommunications systems that applied to many modern telecommunication equipment today. One application is the wifi. Wifi (Wireless Fidelity) is a wellknown tech-nology that utilizes an electronic device to exchange data wirelessly (using radio waves) over a computer network, including high-speed Internet connection, to provide a network connection to all users in the surrounding area. The purpose of this final project is to design microstrip patch antenna built a circular linier array that can be used for signal wifi stronger. The resulting microstrip antenna working in 2.4 GHz band with the acquisition of gain =3.4301 dBi, VSWR = 1.3749 and radiation pattern unidirectional. This antenna design simulation using the software Ansoft High Frequency Structure Simulator v13. For linear circular microstrip patch antenna array then showed its parameters.Keywords: Microstrip Antenna, Wifi, Array, VSWR, Gain